Implications of a Fragile Professional Identity on Role Behavior: An Exploratory Case of an Accountant Fraudster. Issue 4 (8th August 2019) - Dellaportas, Steven; Perera, Luckmika; Gopalan, Sandeep; Richardson, Ben
Abstract: This study explores identity-related issues ensuing from the behavioral choices of a professional accountant who was convicted for defrauding clients of money entrusted to him. It is grounded in data collected from semi-structured interviews with the offender and his companion (partner in life), supplemented with transcripts derived from court hearings. Our findings suggest that the offender was an accidental fraudster whose crime was committed because of his personal traits and because he abandoned an apparently fragile professional identity for a dominant alternative identity. This led the offender to violate professional norms and self-rationalise illegal activity as both temporary and beneficial to his client. Our data illustrate the perils of the professional accountant identity not being firmly established, maintained or regarded as dominant; it enables behavior inconsistent with the professional 'accountant' identity, including criminal activity. This study extends understanding of fraudulent accounting practice by illustrating the role of professional identity in preventing illegal practice in the context of a qualitative forensic case study. It highlights the centrality of professional identity formation, maintenance and reinforcement, particularly in the context of identity conflicts.